My Healing Journey of Catching Tears in a Spoon: Spe'uth's (Bear) Spirituality and Healing Stories Dealing with Complicated Emotions in the Aftermath of Residential School - Martin, Jennifer (City University of Seattle (CityU), 2006)
In this thesis, a Cowichan Native woman researcher records her own healing journey after being incarcerated and forced to attend Residential School. This research addresses a healing and cultural approach for the management of complex and painful emotions. The researcher places her story into a broader context of the suffering experienced by other First Nations people across the land. A descriptive healing process is documented through personal stories and First Nations stories as explanatory tools in a First Nation's methodology. The researcher documents her story and personal challenges in the aftermath of residential school imprisonment and in response to various attempts by federal government to obliterate First Nations culture. The researcher demonstrates the inclusion of Spiritual practice in the study by documenting the role of a Spirit guide Spe'uth. Spe'uth offers her a process of personal and cultural empowerment in a world where European Canadian society continues to violate Aboriginal people through various ongoing forms of neo-colonial practice. This study articulates a healing path for the former prisoners of residential school still dealing with the challenges of cultural repossession through rituals and spirituality.